Prolonged Hemiplegic Migraine Led to Persistent Hyperperfusion and Cortical Necrosis: Case Report and Literature Review - Hu, Yacen; Wang, Zhiqin; Zhou, Lin; Sun, Qiying (Frontiers in Neurology, 2021)
Hemiplegic migraine (HM) is a rare subtype of migraine characterized by aura of motor weakness accompanied by visual, sensory, and/or speech symptoms. Aura symptoms usually resolve completely, permanent attack-related deficit and radiographic change were rare. Here we reported a case presented with progressively aggravated hemiplegic migraine episodes refractory to medication. He experienced two prolonged hemiplegic migraine attacks that led to irreversible visual impairment and cortical necrosis on brain MRI. Multimodal MRI during attack showed persistent vasodilation and hyperperfusion in the affected hemisphere associated with deterioration of clinical symptoms and worsening of brain edema. Patent foramen ovale (PFO) was found on the patient. PFO closure resulted in a significant reduction of HM attacks. This case indicated that prolonged hemiplegic migraine attack could result in irreversible neurological deficit with radiographic changes manifested as cortical necrosis. Persistent hyperperfusion might be an important factor contributing to prolonged attack and persistent attack-related neurological deficit. We recommend screening for PFO in patients with prolonged or intractable hemiplegic migraine, for that closure of PFO might alleviate the attacks thus preventing patient from disabling sequelae.